effect of conjugated linoleic acid supplementation after weight loss on body weight regain, body composition, and resting metabolic rate in overweight subjects - Kamphuis, M.M.J.W; Lejeune, M.P.G.M; Saris, W.H.M; Westerterp-Plantenga, M.S (International Journal of Obesity, 2003)
OBJECTIVE: To study the effects of 13 weeks conjugated linoleic acid (CLA) supplementation in overweight subjects after weight loss on weight regain, body composition, resting metabolic rate, substrate oxidation, and blood plasma parameters. DESIGN: This study had a double-blind, placebo-controlled randomized design. Subjects were first submitted to a very-low-calorie diet (VLCD 2.1 MJ/d) for 3 weeks after which they started with the 13-week intervention period. They either received 1.8 g CLA or placebo per day (low dosage, LD) or 3.6 g CLA or placebo per day (high dosage, HD). SUBJECTS: A total of 26 men and 28 women (age 37.8±7.7 y; body mass index (BMI) 27.8±1.5 kg/m2). MEASUREMENTS: Before VLCD (t=-3), after VLCD but before CLA or placebo intervention (t=0) and after 13-week CLA or placebo intervention (t=13), body weight, body composition (hydrodensitometry and deuterium dilution), resting metabolic rate, substrate oxidation, physical activity, and blood plasma parameters (glucose, insulin, triacylglycerol, free fatty acids, glycerol and β-hydroxy butyrate) were measured. RESULTS: The VLCD significantly lowered body weight (6.9±1.7%), %body fat, fat mass, fat-free mass, resting metabolic rate, respiratory quotient and plasma glucose, insulin, and triacylglycerol concentrations, while free fatty acids, glycerol and β-hydroxy butyrate concentrations were increased. Multiple regression analysis showed that at the end of the 13-week intervention, CLA did not affect %body weight regain (CLA LD 47.9±88.2%, CLA HD 27.4±29.8%, Placebo LD 32.0±42.8%, Placebo HD 22.5±37.9%). The regain of fat-free mass was increased by CLA (LD 6.2±3.9, HD 4.6±2.4%) compared to placebo (LD 2.8±3.2%, HD 3.4±3.6%), independent of %body weight regain and physical activity. As a consequence of an increased regain of fat-free mass by CLA, resting metabolic rate was increased by CLA (LD 12.0±11.4%, HD 13.7±14.4%) compared to placebo (LD 9.1±11.0%, HD 8.6±8.5%). Substrate oxidation and blood plasma parameters were not affected by CLA. CONCLUSION: In conclusion, the regain of fat-free mass was favorably, dose-independently affected by a 13-week consumption of 1.8 or 3.6 g CLA/day and consequently increased the resting metabolic rate. However, it did not result in improved body weight maintenance after weight loss.